Testimonios of leadership: experiences of queer Chicana/Latina administrators in higher education - Rivera, Carmen, author; Muñoz, Susana, advisor; Sisneros, Kathy, committee member; Washington, Jamie, committee member; DeMirjyn, Maricela, committee member (Colorado State University. Libraries, 2019)
The purpose of this study was to examine the leadership experiences of out, queer, Chicana/Latina higher education administrators. These professionals are not only underrepresented numerically, they are also often the only one—or one of few—in their departments or divisions. Grounded in critical race theory, LatCrit, and Chicana Feminist Epistemology, this study conceptualized the ways in which the participants navigated and negotiated their experiences of oppression. The methods of testimonio and pláticas were used to gather the data in a way that also included my own experiences and perspectives as the researcher in a reflexive process. The findings not only reflected the real consequences of oppression for these participants, but the dynamic ways in which they consistently addressed the isms and phobias they faced. Using Anzaldúa's (2015) Coyolxauhqui Imperative as a guide, the two main themes identified were: (1) unmaking: the sources of fragmentation and (2) making and remaking. The sources of fragmentation themes illuminate the many ways in which the participants' lives and experiences were fragmented by oppression and the subthemes included: the labor of oppression parkour and consequences for living and leading from a place of authenticity. The making and remaking themes refer to how similar to the the Coyolxauhqui Imperative, these participants addressed the fragmenting experiences through rebuilding and the subthemes included: thriving in nepantla and intentional healing for nos/otras. The testimonios of the participants offer insights to how to create new, more equitable realities in higher education and leadership via their transformative and iterative process of critical liberatory praxis.
Keywords: higher education; queer; Chicana/Latina; testimonio; leadership